Profil Cedera Olahraga pada Atlet Pencak Silat Kategori Tanding Kontingen Jawa Tengah pada POMNAS XIX Jawa Tengah 2025 - Athallah, Miftah Hafidh; Warthadi, Anugrah Nur; Sudarmanto, Eko (SPRINTER: Jurnal Ilmu Olahraga, 2026)
This study aims to analyze the profile of sports injuries in pencak silat sparring category athletes from the Central Java contingent at POMNAS XIX 2025. This research used a quantitative approach with a descriptive design. The population consisted of 31 athletes, with a sample of 5 injured athletes selected using purposive sampling. The instrument used was a structured questionnaire based on the STROBE-SIIS guidelines. Data were analyzed using descriptive statistics in the form of frequency and percentage. The results showed that all injuries occurred during competition (100%), with the dominant mechanism being direct contact between athletes (66.67%). Based on 11 injury events, injuries were most frequently found in the extremities, particularly the hands and feet (18.18% each). The most common type of injury was bone contusion (60%), followed by fractures and joint dislocations (20% each). The main cause of injury was contact with other athletes (83.33%). The estimated recovery time varied, ranging from no absence to more than six months. In conclusion, injuries in pencak silat sparring athletes are predominantly caused by direct contact, mainly affecting the extremities, with most injuries classified as mild to moderate, although severe injuries still occur. Therefore, comprehensive injury prevention strategies are needed through improved techniques, physical conditioning, and stricter match supervision.